Наближення функцій ермітовими сплайнами з експоненціальними ланками - Пізюр, Я. (Видавництво Національного університету "Львівська політехніка", 2006)
Наведено означення ермітових сплайнів з нелінійними за параметрами виразами в ланках. Виведено формули для параметрів ермітових сплайнів з експоненціальними ланками. Доведено теореми про можливість зведення наближення функцій ермітовими сплайнами з експоненціальними ланками до многочленних ермітових сплайнів. Наведено формули для похибок наближення ермітовими сплайнами. The definition of Hermite splines with non-linear for parameters expressions in links is given. The formulas for parameters Hermite splines with exponential links are deduced. The possibility theorems about reductions approximation of functions by Hermite splines with exponential links to polynomial Hermite splines is proved. The formulas for approximation errors by Hermite splines are given.The definition of Hermite splines with non-linear for parameters expressions in links is given. The formulas for parameters Hermite splines with exponential links are deduced. The possibility theorems about reductions approximation of functions by Hermite splines with exponential links to polynomial Hermite splines is proved. The formulas for approximation errors by Hermite splines are given.
Approximation of functions by hermite splines with exponential links
Keywords: ермітові сплайни; експоненціальна ланка; похибка апроксимації; балансне наближення; Hermite splines; exponential link; error of approximation; balanced approximation